Factor representations of infinite semi-direct products - Zekri, R. (Methods of Functional Analysis and Topology, 2011)
In this article, we propose a new method to study unitary representations of inductive limits of locally compact groups. For the group of infinite upper triangular matrices, we construct a family of type III factorial representations. These results are complements to previous results of A. V. Kosyak, and Albeverio and Kosyak [1, 5].